Knowledge and intentions regarding the Pap smear test among Saudi Arabian women. - Nawal A Alissa (Public Library of Science (PLoS), 2021)
Background The knowledge of Pap smear and uptake of preventive behaviors to prevent cervical cancer are the most important contributors to the advanced stage of the disease. Knowledge is one of the most leading factors to predict the health behaviors and a helpful factor in performing screening procedures. This study aimed to investigate Saudi Arabian women knowledge of Pap testing in relation to their intention to undergo the test. Methods An online survey including demographic characteristics (3 questions), knowledge (13 questions), and intentions (3 questions) towards Pap smear was completed by 467 Saudi Arabian women. Data were analyzed through SPSS version 22, using descriptive statistics and correlation to measure the relationship between knowledge, demographic factors, and intention. Results The study found that average level of knowledge was 1.3 which is between high and moderate knowledge, and the average score for the intention was 2.88, to indicate that the intentions to uptake Pap smear among the participants were above the average. The study revealed a significant correlation between demographic factors and intention (p<0.01). Conclusion Findings from the current study can inform health care providers about Saudi Arabian women knowledge of Pap smear and the intention to uptake the test. Strategies to motivate women to undergo Pap screening should be introduced.